The Physical and Mechanical Properties of Glulam Made from Pine and Jabon Woods - Andi SRD Lestari; Yusuf Sudo Hadi; Dede Hermawan; Adi Santoso (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Wood from plantation forests can be used to make glued laminated lumber (glulam) products for structural applications. Wood from two species, namely pine (Pinus merkusii) and jabon (Anthocephalus cadamba), and polyurethane and tannin mahogany adhesives (glue spread 200 g m-2) were used to manufacture glulams. The aim of this research was to determine the physical and mechanical properties of glulam made from pine and jabon woods. Wood densities of pine and jabon were 0.71 and 0.43 g cm-3, respectively. The glulams consisted of three layers of the same wood species, and samples were (3×6×120) cm3 in thickness, width, and length, respectively. The physical and mechanical properties of glulam were tested according to Japanese Agricultural Standard (JAS) 234-2007. The results showed that glulam made from pine met the standard for modulus of elasticity and modulus of rupture (MOR) values. Glulam made from jabon wood fulfilled the standard for MOR, shear strength, and hot- and cold-water delamination tests. In the formaldehyde emission test, jabon glulam fulfilled the F*** (low emission) standard and pine glulam met the F**** (very low emission) standard according to JAS 234-2007.